Layered Potassium Titanium Niobate/Reduced Graphene Oxide Nanocomposite as a Potassium-Ion Battery Anode - Nason, Charlie A. F.; Saroja, Ajay Piriya Vijaya Kumar; Lu, Yi; Wei, Runzhe; Han, Yupei; Xu, Yang (Nano-Micro Letters, 2023)
With graphite currently leading as the most viable anode for potassium-ion batteries (KIBs), other materials have been left relatively under-examined. Transition metal oxides are among these, with many positive attributes such as synthetic maturity, long-term cycling stability and fast redox kinetics. Therefore, to address this research deficiency we report herein a layered potassium titanium niobate KTiNbO5 (KTNO) and its rGO nanocomposite (KTNO/rGO) synthesised via solvothermal methods as a high-performance anode for KIBs. Through effective distribution across the electrically conductive rGO, the electrochemical performance of the KTNO nanoparticles was enhanced. The potassium storage performance of the KTNO/rGO was demonstrated by its first charge capacity of 128.1 mAh g−1 and reversible capacity of 97.5 mAh g−1 after 500 cycles at 20 mA g−1, retaining 76.1% of the initial capacity, with an exceptional rate performance of 54.2 mAh g−1 at 1 A g−1. Furthermore, to investigate the attributes of KTNO in-situ XRD was performed, indicating a low-strain material. Ex-situ X-ray photoelectron spectra further investigated the mechanism of charge storage, with the titanium showing greater redox reversibility than the niobium. This work suggests this low-strain nature is a highly advantageous property and well worth regarding KTNO as a promising anode for future high-performance KIBs. Highlights: 1 KTiNbO5 and KTiNbO5/reduced graphene oxide (rGO) nanocomposites were successfully synthesised via solvothermal methods. Optimising the rGO wt% yielded a composite with 12 wt% (KTNO/rGO-12). 2 KTNO/rGO-12 was tested for its potassium storage performance, achieving a first charge capacity of 128.1 mAh g−1 and retaining 76.1% over 500 cycles at 20 mAh g−1. 3 The mechanism of intercalation was examined, suggesting a potentially low-strain material, with both titanium and niobium redox activity contributing to the charge storage.